Improving board effectiveness through learning : an examination of learning interventions for the performance of boards : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Palmerston North, New Zealand - Allen, Peter Horace (Massey University, 2022)
Organisations face a plethora of internal and external challenges, and these challenges are, by definition, learning challenges. As fiduciaries of organisational purpose, boards have the ultimate responsibility for their organisations; therefore, the challenges are board learning challenges. Board learning for individual members and as a collective group has largely been ignored in the governance literature, and this research seeks to contribute insight into board learning processes occurring in the boardroom and the elements that contribute to board effectiveness. It is in the interests of society that boards learn to make sound decisions because board decisions affect all members of society. However, more education does not automatically result in effective learning. This research aims to understand instances of governance and learning and how the findings bear upon theory and develop propositions that link governance and learning concepts. The research employed a mixed-methods research design and semi-structured interviews with 26 directors or trustees from small and medium-sized for-profit and not-for-profit organisations. The results show that learning was integral to governance and axiomatic to the fiduciary’s duty. Unambiguous links were manifest between board learning and board effectiveness. The research revealed knowledge of the learning characteristics that are most likely to affect board effectiveness and developed six propositions that include specific board learning practices applicable to board meetings and explicit realms of learning responsibility that are also either hindrances or enablers of learning. Hindrances to learning included the inability to acknowledge that learning was required. A safe zone for robust discussion was an important enabler of learning.
Figures 2.2 & 7.3 (=Crow & Lockhart, 2016, Fig 1 p. 1031) have been removed for copyright reasons.
Keywords: corporate governance; board learning; board effectiveness; hubris; safe zone; fiduciary; learning hindrances; learning enablers; organisational performance